Action potential clamp characterization of the S631A hERG mutation associated with short QT syndrome. Issue 17 (2nd September 2018) - Butler, Andrew; Zhang, Yihong; Stuart, Alan G.; Dempsey, Christopher E.; Hancox, Jules C.
Abstract: The hERG potassium channel is critical to normal repolarization of cardiac action potentials (APs) and loss‐ and gain‐of‐function hERG mutations are associated, respectively, with long and short QT syndromes, pathological conditions that can lead to arrhythmias and sudden death. hERG current ( I h ERG ) exhibits uniquely fast inactivation involving conformational changes to the channel pore. The S631A hERG pore mutation was originally engineered to interrogate hERG channel inactivation, but has very recently been found in a family with short QT syndrome (SQTS). Accordingly, this study characterized the effects of the S631A mutation on I h ERG profile during ventricular, atrial, and Purkinje fiber (PF) AP waveforms, using patch clamp recording from hERG expressing HEK 293 cells at 37°C. Under conventional voltage clamp, the current–voltage ( I – V ) relation for I h ERG exhibited a marked right‐ward shift in the region of negative slope at positive membrane potentials. Under ventricular AP clamp, the S631A mutation resulted in augmented I h ERG, which also peaked much earlier during the AP plateau than did wild‐type (WT) I h ERG . Instantaneous I – V relations showed a marked positive shift in peak repolarizing current during the ventricular AP in the S631A setting, while the instantaneous conductance‐voltage relation showed an earlier and more sustained rise in S631A compared to WT I h ERG conductance during ventricular repolarization. Experiments with atrial and PF APs in each case also showed augmented and positively shifted I h ERG in the S631A setting, indicating that the S631A mutation is likely to accelerate repolarization in all three cardiac regions. Ventricular AP clamp experiments showed retained effectiveness of the class Ia antiarrhythmic drug quinidine (1 μ mol/L) against S631A I h ERG . Quinidine is thus likely to be effective in reducing excessively fast repolarization in SQTS resulting from the S631A hERG mutation. Abstract : The S631A hERG attenuated inactivation mutation has recently been found in a family with short QT syndrome. The mutation increases and alters the timing of hERG current during ventricular, atrial, and Purkinje fiber action potentials. Quinidine retains effectiveness against S631A hERG under action potential voltage clamp and so may be useful therapeutically against this mutation.